PEMANFAATAN EKSTRAK AKAR ALANG – ALANG (Imperata cylindrica L.) SEBAGAI HERBISIDA PRATUMBUH - Hadriman Khair; Khairunnas ,; Tarekh Kemal Daulay; Dani Prayoga; Muhammad Khoiruddin (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2012)
AbstractNatural herbicides is an effort to improve the competitiveness of the quality and quantity of production. Although the tall grass (Imperata cylindrica L.) is a weed, but this plant can be used as a herbicide to suppress the growth of weed seeds in the soil. The study was conducted to determine the effectiveness of grass root extract in suppressing the growth of weed seeds in the soil. The research was conducted in the home garden experiment pads Faculty of Agriculture, University of North Sumatra Muhammadiyah Jln. Tuar no. Medan District 65 Sand with altitude ± 27 m above sea level and implemented from the month of February 26, 2012 to 23 April 2012. Using a Completely Randomized Design (CRD) factorial with 10 treatments and 3 replicates and tested using Duncant test (DMRT). With the concentration of A0 = 0%, A1 = 15%, A2 = 30%, A3 = 45%, A4 = 60%. In this research found that the degree of concentration of 15% significantly affect the period of germination, mortality, and length of primary roots. In this research found that the degree of concentration of 15% significantly affect the period of germination, mortality, and length of primary roots. In this study differences in the doses used in the treatment level is too low at 15%. So the difference in the data obtained is not significant among all the standard treatments. But the results of research with a concentration of 30% is in treatment in the use of extracts A2G2 alang - alang more effective against the primary root length on weeds and spinach shy daughter of thorns. For mortality, the use of extracts of grass - grass is more effective in the treatment of spinach burr weed.Keywords: Weeds, Herbicides natural alang – alang